Rules Limiting Athletic Performance or Prohibiting Athletic Participation for Health Reasons - Matthew J. Mitten (University of Kansas Libraries, 2009)
This article analyzes the paradox between: 1) intercollegiate sport's objectives of maximizing athletic performance and providing athletic participation opportunities to those possessing the requisite physical ability and skills to compete successfully; and 2) National Collegiate Athletic Association rules that limit athletic performance by all student-athletes, or university requirements that prohibit individual student-athletes from participating in intercollegiate sports, for health reasons. Some student-athletes seek to maximize athletic performance by taking performance-enhancing substances, even if doing so creates potential future adverse health effects. Others may want to participate in intercollegiate sports with a physical abnormality and are willing to assume an increased risk or severity of injury beyond that inherent in the sport. However, the NCAA and its member universities, as producers and regulators of intercollegiate sports, have valid legal authority and ethical grounds to promulgate and enforce health, safety, and competition rules that limit the autonomy interests of adult student-athletes.